VOICES: Case Study of a Faculty Development Program in Multicultural Education at an AANAPISI 2-Year College - Gimness, Erik (My University, 2022)
As higher education institutions continue to focus more on equity and allocating resources to serve historically marginalized populations, community colleges in particular have benefited from programs such as the federal Asian American and Native American Pacific Islander Serving Institution (AANAPISI) grants to help fund such efforts. One thread of scholarly inquiry looks at how these funds can be used to help improve the outcomes of Asian and Pacific Islander students. This study seeks to understand how leaders of a professional development program at an AANAPISI-designated urban community college integrated multicultural education to better prepare faculty to teach diverse students—specifically Asian American and Pacific Islander (AAPI) students—and how the faculty responded to this professional development process. Case study evidence of success (change in knowledge, skills, and practice among innovators) reveals ways in which a grant-funded multicultural faculty professional development focused on serving and creating a culturally responsive learning environment for AAPI students can result in lasting and sustainable change. The findings from this study provide evidence that VOICES program leaders demonstrated the ability to incorporate multicultural education into the VOICES program, which facilitated professional development as evidenced by faculty perceptions of the program and descriptions of their own changing knowledge, skill, and practice. Furthermore, evidence revealed an emergent community of practice (CP) that persisted beyond the VOICES program and lifespan of the AANAPISIS grant. Despite these successes, however, there were also challenges that surfaced in the study that inhibited the program’s success and sustainability, although most of these were addressed through various types of support, advocacy and collaboration. The study has produced eight themes that relate to challenges and supports on how multicultural education was incorporated into the professional development program. Three of the themes describe challenges to the program, including (1) difficulty scaling impact of changes to practice beyond the program; (2) internal resistance to serving special populations; and (3) differing views on support expectations. Five of the themes illustrate elements of support for the program, including (1) shared understanding of the role of the program; (2) faculty knowledge and practice around culturally responsive teaching; (3) support of leaders from the VOICES program, faculty, and the college; (4) changes to hiring practices associated with diversity goals; and (5) strong ties to local community.
Thesis (Ph.D.)--University of Washington, 2022
Keywords: AANAPISI; Asian; Community College; Faculty Development; Federal Grant Programs; Pacific Islander; Higher education administration; Multicultural education; Educational evaluation; Education - Seattle